Comparison of the Effectiveness of Chewing Pineapple and Jicama on Reducing Debris Index in Sidoarjo: A Quasi-Experimental Study - Ayu pratiwi trisnawati; Sri Hidayati; Silvia Prasetyowati; Sunomo Hadi (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
ABSTRACT School-age children aged between 6-12 years are one of the groups most vulnerable to experiencing dental and oral health problems. In school-age children, consuming sticky foods tends to stick to their teeth and can cause dental problems. Debris is food waste that contains bacteria. Different from plaque and white material, debris is easier to clean. Chewing fibrous foods is a natural way to control plaque or debris. Fibrous and watery foods such as pineapple and jicama fruit can clean the surface of the teeth by chewing them. because these fruits have the ability to clean teeth which have self-cleaning capabilities. Research Objective: This study aims to determine the difference in the effectiveness of chewing pineapple and jicama fruit on reducing the debris index in class V students at SDN Pagerwojo Sidoarjo. Method: The type of research carried out was Quasi Experimental with a pretest and posttest design. The subjects of this research consisted of 86 class V students at SDN Pagerwojo. The data collection method uses a debris index inspection sheet by making direct observations of respondents. The data analysis technique used is the Shapiro-Wilk test if the data is normally distributed, if the data is not normally distributed using the Wilcoxson test. Results: The results of the research that has been carried out can be concluded that there is a difference in the effectiveness of chewing pineapple and jicama fruit in reducing index debris, that chewing jicama fruit is more effective in reducing index debris than chewing pineapple fruit.